2002
DOI: 10.1152/ajplung.00305.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of anti-L-selectin antibody in burn and smoke inhalation injury in sheep

Abstract: We hypothesized that the antibody neutralization of L-selectin would decrease the pulmonary abnormalities characteristic of burn and smoke inhalation injury. Three groups of sheep ( n = 18) were prepared and randomized: the LAM-(1–3) group ( n = 6) was injected intravenously with 1 mg/kg of leukocyte adhesion molecule (LAM)-(1-3) (mouse monoclonal antibody against L-selectin) 1 h after the injury, the control group ( n = 6) was not injured or treated, and the nontreatment group ( n = 6) was injured but not tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Accordingly, in the present study, we also showed that combined anticoagulant therapy significantly reduced the increase in lung tissue MPO activity. We have also shown previously that inhibition of L-selectin resulted in a marked reduction in pulmonary transvascular fluid flux and lung oedema [29]. Antithrombin suppresses leucocyte activation through inhibiting NF-κB [30] and affects neutrophil migration via its heparin-binding site interacting with cell-surface syndecan-4 [5,31], a transmembrane receptor expressed on multiple cell types including neutrophils.…”
Section: Discussionmentioning
confidence: 73%
“…Accordingly, in the present study, we also showed that combined anticoagulant therapy significantly reduced the increase in lung tissue MPO activity. We have also shown previously that inhibition of L-selectin resulted in a marked reduction in pulmonary transvascular fluid flux and lung oedema [29]. Antithrombin suppresses leucocyte activation through inhibiting NF-κB [30] and affects neutrophil migration via its heparin-binding site interacting with cell-surface syndecan-4 [5,31], a transmembrane receptor expressed on multiple cell types including neutrophils.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, L-selectin antagonists could interfere with neutrophil adhesion. In experimental studies, blocking of Lselectin reduced the remote lung injury after infrarenal ischemia reperfusion injury (6) without increasing the risk of infection, improved survival in a baboon trauma model (7), and diminished pulmonary microvascular permeability in burn and smoke injury (8). In view of the experimental studies, as well as the role of L-selectin in the development of posttraumatic organ failure (9), blocking L-selectin may also attenuate recruitment of leukocytes in the posttraumatic inflammatory response and, thus, might decrease the rate of MOF in multiple traumatized patients.…”
mentioning
confidence: 99%
“…There are several studies reporting that selectins might be involved in cell activation [16]. This may be why we were able to block much of the pulmonary microvascular response with the administration of LAM1-3, the F(ab) # portion of the monoclonal antibody to L-selectin [3,17]. The anti-(P-selectin) antibody may not prevent the activation process involved in deposition of leucocytes in the pulmonary microcirculation (i.e.…”
Section: Discussionmentioning
confidence: 83%